2015
DOI: 10.3389/fneur.2015.00222
|View full text |Cite
|
Sign up to set email alerts
|

The Quest to Model Chronic Traumatic Encephalopathy: A Multiple Model and Injury Paradigm Experience

Abstract: Chronic neurodegeneration following a history of neurotrauma is frequently associated with neuropsychiatric and cognitive symptoms. In order to enhance understanding about the underlying pathophysiology linking neurotrauma to neurodegeneration, a multi-model preclinical approach must be established to account for the different injury paradigms and pathophysiologic mechanisms. We investigated the development of tau pathology and behavioral changes using a multi-model and multi-institutional approach, comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 48 publications
(44 reference statements)
1
25
0
1
Order By: Relevance
“…130 A series of contributions from Petraglia et al [131][132][133][134] have described the pathological and behavioral effects of repetitive TBI in a closed skull model of TBI in mice and demonstrated the clearly greater effects of multiple impacts on a variety of behavioral measures. While much attention has been focused on the cellular (both neural and glial) response to TBI, as well as its behavioral consequences, less attention has been directed toward understanding possible effects of TBI on cerebral vasculature.…”
Section: Comparison Of Single Vs Multiple Impactsmentioning
confidence: 99%
“…130 A series of contributions from Petraglia et al [131][132][133][134] have described the pathological and behavioral effects of repetitive TBI in a closed skull model of TBI in mice and demonstrated the clearly greater effects of multiple impacts on a variety of behavioral measures. While much attention has been focused on the cellular (both neural and glial) response to TBI, as well as its behavioral consequences, less attention has been directed toward understanding possible effects of TBI on cerebral vasculature.…”
Section: Comparison Of Single Vs Multiple Impactsmentioning
confidence: 99%
“…We found that ER stress is increased in cells that are undergoing apoptosis as well as those that develop tauopathy [25]. The key markers that were increased were markers of tau hyperphosphorylation AT100, PHF, and CP-13 [26]. It is apparent that tau hyperphosphorylation is an end-stage marker.…”
Section: Current Understanding Of Ctementioning
confidence: 81%
“…Similar to blast injury, increases in tau phosphorylation and pathologic tau conformations have been found one month following a single closed head injury (Turner et al , 2015). However, other studies have shown a requirement for repeat injuries in order to induce tau pathology following closed head injury.…”
Section: Tbi Tau and Cte - The Animal Modelsmentioning
confidence: 98%
“…Tau phosphorylation and pathologic tau conformations are increased in rat hippocampus and cortex one month following either a single blast or six blasts spaced 48h apart (Turner et al , 2015). Furthermore, rats exposed to repeat injury showed evidence of perivascular tau pathology, a defining feature of human CTE (Turner et al , 2015).…”
Section: Tbi Tau and Cte - The Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation